STUDY OF HEAVY METAL LEAD (PB) IN THE NORTHERN WATERS OF BELITUNG REGENCY - Fathona, Salsabila; Rachmayani, Rima; Nurhidayati, Ayu Utami; Utami, Dwi Amanda (Marine Geological Institute of Indonesia, 2025)
Belitung Regency has significant tin potential, spread across the land, rivers, and beaches which have been mined for hundreds of years. However, tin mining activities are indicated to be a source of pollution in the northern region of Belitung Regency. This study aims to determine the distribution of the lead (Pb) concentrations in sediments and water columns in the northern waters of Belitung Regency and to evaluate the seasonal effect, particularly ocean currents, on the distribution patterns. In situ data were collected during the westerly season, including sediment samples, water column samples, and oceanographic parameters such as seawater quality and current measurements. During the easterly season, only sediment samples were obtained. Pb concentrations in sediments and water samples were analyzed at the National Research and Innovation Agency (BRIN) laboratory using the Atomic Absorption Spectrophotometry (AAS) method. The results showed that Pb concentrations in sediment samples ranged from 10.08 to 50.08 mg/kg during the easterly season, and from 10.96 to 60.72 mg/kg during the westerly season. In the water column, Pb concentrations ranged from 0 to 0.05 mg/L during the westerly season. The distribution pattern of Pb in sediments in the easterly season tended to spread offshore, while in the westerly season it is accumulated in the river. These patterns are influenced by seasonal flow variations, geographical location, and sediment grain size. Pb concentrations in sediments are higher in the westerly season compared to the easterly season. This is likely due to increased erosion and surface runoff during the rainy season, which leads to greater deposition of heavy metals in marine sediments.